Konieczność edukacji katechetów w medialny projekt Youcat [The necessity of education for catechists in Youcat media project] - Kiciński, Andrzej (Biuletyn Edukacji Medialnej [Media Education Bulletin], 2014)
Catechism for youth Youcat beats records of popularity. The first empirical study of its reception among the young Polish people been carried out. At the Institute of Pastoral Theology and Catechetics at the Catholic University of Lublin John Paul II P. Ścisłowicz defended his doctoral thesis on this topic. The study showed a high percentage of young people who respond positively to the content and form of Youcat. Results at 70% approval by the youth probably will not be better for a long time. On the other hand, catechists education process will be very long. They need to understand that Youcat will not replace textbooks for the teaching of the Catholic religion in schools, because it is only complementary. It is also about the entry in the digital world where young people spend a lot of time. There is a need for education for catechists on Youcat media project. It is necessary to fully understand this book, with all its history of creation, with its new language, drawings, photographs, definitions, quotes and all the potential transmission of the faith in the modern world of young people. With this project, the living faith of young people and the living faith of the pastors of the Church Benedict XVI is strictly bound.
https://katalog.adlr.link/Record/ai-53-96306